The Effect of Life Skills Training on Emotional Intelligence of the Medical Sciences Students in Iran - Hamideh A Lolaty; Sharbanoo Ghahari; Abdolhakim Tirgari; Jabbar Heydari Fard (Indian Journal of Psychological Medicine, 2012)
Background: Emotional intelligence has a major role in mental health and life skills training, and could be viewed as a bridge relating to emotional intelligence and mental health. Aim: The present study is aimed at determining the effect of life skills training on the emotional intelligence among the first year students of Mazandaran University of Medical Sciences. Materials and Methods: In this experimental study, the subjects were selected by random sampling and allocated into two groups: Case group (n=20) and control group (n=19); they matched for gender, experience of stressful life events in the past six months, level of interest in the field of study, and level of emotional intelligence. The two groups responded to Bar-on Emotional Quotient Inventory before starting the experiment. Subsequently, the case group underwent life skills training. After the training, Bar-on Emotional Quotient Inventory was responded by the case and control groups again. The data was analyzed using descriptive statistics including Chi-square test, paired and independent t-tests, using SPSS software version 15. Results and Conclusion: In the case group, the scores of emotional intelligence after life skills training were significantly improved (t=11.703 df=19 P=0.001), while no significant difference was observed in the control group (t=0.683 df =18 P=0.503). By performing programs such as life skills training, the levels of emotional intelligence of the students could be increased, which itself could lead to academic success, reduced substance abuse, and increased stress tolerance in the students.